School shootings and the strategic contributions of gun policy PACs in US House elections - Eric A. Baldwin; Takuma Iwasaki; John J. Donohue (Proceedings of the National Academy of Sciences, 2026)
The American public consistently supports stricter gun laws. We show that the gun lobby is most concerned that this support will translate into federal legislative action when fatal school shootings occur. Leveraging a dataset of political action committee (PAC) contributions and school shootings, we implement a staggered difference-in-differences design to estimate the causal effect of fatal school shootings on contributions to House candidates. We find progun Political Action Committees increase contributions by 31% to candidates in districts with fatal school shootings, and 20% for gun safety PACs. Neither show any significant response to nonfatal school shootings or mass shootings. The temporal pattern also reveals strategic behavior: For both progun and gun safety PACs, contribution spikes emerge in the wake of fatal school shootings, with effects dramatically amplified as Election Day approaches; when a shooting occurs within two months of Election Day, contributions from progun PACs increase by 2,820% while gun safety PAC contributions increase by 917%. These effects are concentrated in competitive districts ( ≤ 5% margins) where the two-sided surge in contributions offsets any measurable electoral impact. These results provide robust evidence that PACs strategically deploy contributions after school shootings, with the magnitude and timing suggesting a deliberate mobilization to advance its agenda. Our findings underscore a gap in democratic accountability: While public opinion should drive policy change, campaign contributions are wielded to blunt electoral responsiveness, providing insight into the inability of Congress to adopt broadly supported gun safety measures.